ANALISIS MUTU IKAN PATIN (Pangasius sp.) SALAI DENGAN PEMBERIAN KITOSAN DAN LAMA PENGASAPAN SEBAGAI RANCANGAN LKPD BIOLOGI SMA - Sri Wulandari; Elya Febrita; Anugrah Tifanny (Biogenesis, 2021)
The aims to determine the effect of chitosan concentration and smoking time on the quality of smoked catfish (Pangasius sp.) and produce Student Worksheet design. This research was divided into two step, there is experimental step and the Student Worksheet design. At the experimental step, used a factorial Completely Randomized Design (CRD). Factor I is the concentration of chitosan, and factor II is duration of smoking time. This study consisted of 12 treatments with 3 replications so that there were 36 experimental units. Parameters observed were protein content, fat content, water content and organoleptic on appearance, scent, taste and texture. The results showed that the effect of chitosan concentration and smoking time had an effect on treated with 3% chitosan and 3 days of smoking showed the best results, with the total protein content was 35.89%, fat content was 29.72% and water content was 15.27%. Meanwhile, the organoleptic test results of smoked catfish on the aspects of appearance, scent, taste and texture, the best treatment was also found in smoked catfish with 3% chitosan treatment and 3 days of smoking time. The results can be used as a student worksheet design on Food Additives material for class XI high school.